The Basic Approaches to the Value of Life in Bioethical Discourse - Horban, Oleksandr; Martych, Ruslana (Studia Warmińskie, 2022)
The article is devoted to the study of the understanding of life in bioethical discourse, axiological determinants of understanding “life” in modern bioethical research. The authors note that in the current crisis conditions, the value of life as a unique phenomenon of the manifestation of the beingness of the living increases immeasurably. All the variety of points of view and approaches to determining the value of life in bioethical discourse can be grouped into two main approaches, which can be conditionally called the ethics of sacredness (sanctity) of life and the ethics of the quality of life. Being oppositional in their views to each other, these approaches have a great scientific potential, allowing the development of bioethical doctrine through the formation of moral norms and imperatives of human behavior and the establishment of the boundaries of human influence on the ways and forms of existence of the living.